Primeval very low-mass stars and brown dwarfs – IV. New L subdwarfs, Gaia astrometry, population properties, and a blue brown dwarf binary. Issue 4 (31st July 2018) - Zhang (张曾华), Z H; Galvez-Ortiz, M C; Pinfield, D J; Burgasser, A J; Lodieu, N; Jones, H R A; Martín, E L; Burningham, B; Homeier, D; Allard, F; Zapatero Osorio, M R; Smith, L C; et al.
ABSTRACT: We present 27 new L subdwarfs and classify five of them as esdL and 22 as sdL. Our L subdwarf candidates were selected with the UKIRT Infrared Deep Sky Survey and Sloan Digital Sky Survey. Spectroscopic follow-up was carried out primarily with the OSIRIS spectrograph on the Gran Telescopio Canarias. Some of these new objects were followed up with the X-shooter instrument on the Very Large Telescope. We studied the photometric properties of the population of known L subdwarfs using colour-spectral type diagrams and colour–colour diagrams, by comparison with L dwarfs and main sequence stars, and identified new colour spaces for L subdwarf selection/study in current and future surveys. We further discussed the brown dwarf transition-zone and the observational stellar/substellar boundary. We found that about one-third of 66 known L subdwarfs are substellar objects, with two-thirds being very low-mass stars. We also present the Hertzsprung–Russell diagrams, spectral type–absolute magnitude corrections, and tangential velocities of 20 known L subdwarfs observed by the Gaia astrometry satellite. One of our L subdwarf candidates, ULAS J233227.03+123452.0, is a mildly metal-poor spectroscopic binary brown dwarf: a ∼L6p dwarf and a ∼T4p dwarf. This binary is likely a thick disc member according to its kinematics.